234k views
3 votes
If h(x) = 5 + x and k (x) = StartFraction 1 Over x EndFraction, which expression is equivalent to (k circle h) (x)?

2 Answers

1 vote

Answer:

The answer is B

Explanation:

User Sqeezer
by
5.7k points
1 vote

Answer:

The equivalent expression to
(k\circ h)(x) is
(1)/(5+x)

Therefore
(k\circ h)(x)=(1)/(5+x)

Explanation:

Given that the functions h is defined by h(x)=5+x

and k is defined by
k(x)=(1)/(x)

To find the composition of k and h that is
(k\circ h)(x) :


(k\circ h)(x)=k(h(x))


=k(5+x)


=(1)/(5+x)

Therefore
(k\circ h)(x)=(1)/(5+x)

The equivalent expression to
(k\circ h)(x) is
(1)/(5+x)

User J Fabian Meier
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.